2017
DOI: 10.1111/jth.13606
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding risk of terminally ill patients hospitalized in palliative care units: the RHESO study

Abstract: Background The value of primary thromboprophylaxis in patients admitted to palliative care units is debatable. Moreover, the risk of bleeding in these patients is unknown. Objectives Our primary aim was to assess the bleeding risk of patients in a real-world practice setting of hospital palliative care. Our secondary aim was to determine the incidence of symptomatic deep vein thrombosis and to identify risk factors for bleeding. Patients/Methods In this prospective, observational study in 22 French palliative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
0
40
0
1
Order By: Relevance
“…With regards to PCU, a retrospective analysis at Genevan PCU showed that TPX was used in 43% of cancer patients [18]. Likewise, the TPX prevalence was high (44%) in a French study, which enrolled 1199 PCU patients, 91% of whom were cancer patients [19]. A cross-sectional study on the prevalence of TPX among 134 PCU patients in Austria revealed that primary and secondary TPX was used in 49% of cancer patients, similarly to non-cancer patients (42%) [20], although there was a tendency to discontinuation of TPX upon admission to PCU.…”
Section: Prevalence Of Thromboprophylaxis In Hospices and Palliative mentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to PCU, a retrospective analysis at Genevan PCU showed that TPX was used in 43% of cancer patients [18]. Likewise, the TPX prevalence was high (44%) in a French study, which enrolled 1199 PCU patients, 91% of whom were cancer patients [19]. A cross-sectional study on the prevalence of TPX among 134 PCU patients in Austria revealed that primary and secondary TPX was used in 49% of cancer patients, similarly to non-cancer patients (42%) [20], although there was a tendency to discontinuation of TPX upon admission to PCU.…”
Section: Prevalence Of Thromboprophylaxis In Hospices and Palliative mentioning
confidence: 99%
“…In the only one randomized study investigating prophylactic LMWH vs. placebo in 20 PCU patients with a life expectancy of ≤6 months, one VTE and one major bleeding occurred in the group receiving nadroparin (p = 1), whereas two minor bleedings occurred in the control group (p = 0.474) [11]. More light on bleeding risk in terminally ill PCU patients has been shed by a multicenter observational RHESO study [19]. Among twelve hundred patients on the study group, the majority of whom were cancer patients (91%), 44% were receiving primary or secondary TPX using LMWH or fondaparinux.…”
Section: Risks and Challengesmentioning
confidence: 99%
“…Multivariate analysis identified that bleeding was associated with thromboprophylaxis (p=0.04, HR = 1.48 (1.02-2.15)), suggesting that the bleeding risks of VTE prophylaxis might outweigh the benefits in this population. 20 The Hospice Inpatient Deep Vein Thrombosis Detection study has recently been published and further challenges the perceived benefit of pharmacological thromboprophylaxis. 21 In this prospective longitudinal observational study, 343 cancer patients underwent bilateral femoral vein ultrasonography on admission and weekly until death or discharge.…”
Section: Primary Thromboprophylaxismentioning
confidence: 99%
“…Another observational study involving nearly 1200 patients admitted to palliative care wards, 90% of whom had malignancies, demonstrated a low incidence of VTE. In nearly 10% of patients clinically significant bleeding was observed and was associated primarily with prophylactic anticoagulation [52]. On the basis of these data, LMWH anticoagulation prophylaxis in hospice patients would seem to be inadvisable.…”
Section: Anticoagulation Therapy and The Use Of Doac In Hospice Patientsmentioning
confidence: 96%